13. The Systematic of the Characters from the Opera a Stormy Night by Paul Constantinescu - Radu-Țaga Consuela (Sciendo, 2020)
In the history of the Romanian musical theatre the comic opera A Stormy Night written by Paul Constantinescu set up the buffa style. All along the two acts carried out in approximately 50 minutes you can hear Romanian folklore resonances, with Anton Pann echoes, as the 7 characters from the opera live in the Bucharest of the 19th century. The leitmotif technique is at the basis of the musical story, 9 melodious-rhythmic configurations getting detached. The musical discourse of the singers is entirely subordinated to the text, and the ample breath appeals to the recitative singing, which evolves towards arioso. The categorical overlapping of the musical declamation with the spoken language initiates a route in which we encounter phenomena such as sprechgesang, parlato, yelling, buffa slipping of the voice. The characters are X-rayed with a deep critical spirit and the capacity to illustrate funny situations gains a lot from Constantinescu's experience.